2020
DOI: 10.1111/ejh.13392
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pixantrone for the treatment of multiply relapsed or refractory aggressive non‐Hodgkin B‐cell lymphomas

Abstract: Eur J Haematol. 2020;104:499-508. | 499 wileyonlinelibrary.com/journal/ejh 1 | INTRODUC TI ON Diffuse large B-cell lymphoma (DLBCL) is the most common form of non-Hodgkin lymphoma (NHL); between 30% and 58% of patients with NHL have DLBCL, which has a crude incidence in Europe of 3.81 cases per 100 000. 1,2 The incidence of both NHL and DLBCL varies considerably between European countries, with Italy and Spain having an incidence of NHL higher than the European average. 1-3 First-line therapy for intermediate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…10,11 However, the phase III study PIX306, comparing the efficacy and safety of pixantrone with rituximab (PIX-R) versus gemcitabine with rituximab (GEM-R) in patients with relapsed (not refractory) aggressive B-cell NHL, deemed ineligible for ASCT (NTC01321541), failed to demonstrate any improvement in outcomes with pixantrone and rituximab as opposed to gemcitabine with rituximab. [12][13][14] In line with this were also findings of some real-world studies [15][16][17] which have shown overall disappointing outcomes of treatment with pixantrone and have therefore questioned the actual role of pixantrone in the current treatment of R/R aggressive lymphomas.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…10,11 However, the phase III study PIX306, comparing the efficacy and safety of pixantrone with rituximab (PIX-R) versus gemcitabine with rituximab (GEM-R) in patients with relapsed (not refractory) aggressive B-cell NHL, deemed ineligible for ASCT (NTC01321541), failed to demonstrate any improvement in outcomes with pixantrone and rituximab as opposed to gemcitabine with rituximab. [12][13][14] In line with this were also findings of some real-world studies [15][16][17] which have shown overall disappointing outcomes of treatment with pixantrone and have therefore questioned the actual role of pixantrone in the current treatment of R/R aggressive lymphomas.…”
Section: Introductionmentioning
confidence: 69%
“…41,42 Following the pivotal PIX301 study, there were two real-life studies on pixantrone in monotherapy; one UKwide retrospective study of R/R DLBCL patients 15 and the other -the PIXA study conducted in Spain and Italy including the same patient population, that is, patients with aggressive relapsed or refractory B-cell NHL who had progressed after two or more prior therapies. 16 Patients from the Eyre and coworkers' study had poorer prognostic features than those from the PIX301 trial; 85% had refractory disease and 72% had an international prognostic index (IPI) value of 3 to 5 at commencement of pixantrone. The median PFS was 2.0 months and the median OS 3.4 months.…”
Section: Treatment Of R/r Patientsmentioning
confidence: 99%
See 3 more Smart Citations